“Ontem, Simonton. Hoje, McIntire": o surgimento e o desenvolvimento da Igreja Presbiteriana Fundamentalista do Brasil na cidade do Recife (1956-1995). - Souza, José Roberto de (2020)
The research sought to analyze the emergence and development of the Igreja Presbiteriana Fundamentalista do Brasil (IPFB - Fundamental Presbyterian Church of Brazil), being the result of a schism of the Igreja Presbiteriana do Brasil (IPB - Presbyterian Church of Brazil), which took place in the city of Recife in 1956. In the mid-twentieth century, the fundamentalist American protestant movement attracted supporters of the Presbyterian Church of Brazil (IPB) in the city of Recife. The main leader of the movement was Reverend Israel Gueiros (1907-1996), who stood out as spokesman for the movement in the city. The organization of this new religious movement, product of the numerous clashes between the Rev. Israel and his former denomination, resulted in his ecclesiastical discipline, and subsequent "detachment" from the denomination. Therefore, the beginning of the IPFB's foundation was analyzed, following the examination of the “Brasil Presbiteriano” (“Presbyterian Brazil”, belonging to the IPB) and “A Defesa” (“The Defense”, belonging to the IPFB), as well as some minutes of the Presbitério de Pernambuco (Presbytery of Pernambuco), the Seminário Presbiteriano do Norte (SPN - North Presbyterian Seminary) Teachers' Congregation and some other documents from the IPB and IPFB councils. Through these sources, and using Pierre Bourdieu's sociological theoretical observations about the “field,” the differences between the groups that ran these denominations are noticeable, including the arguments and strategies used by the IPB in the fight against fundamentalists. as well as the accusations and arguments made by Rev. Israel Gueiros to the IPB, which affirmed the need to open a new seminar in the city of Recife. Thus, we realize that these clashes were mainly due to the loss of ecclesiastical political space on the part of Rev. Israel Gueiros, rather than a discourse regarding a detriment or threat to orthodoxy. Thus, this research contributes to the discussions about how the academy can advance in its understanding about the theme of Protestant Fundamentalism in Brazil.